ANALISIS PERJANJIAN PRA NIKAH YANG DILANGSUNGKAN DI DALAM PERKAWINAN MENURUT HUKUM POSITIF DI INDONESIA - Vito Qobul Choliek; Susilo Wardani (Collegium Studiosum Journal, 2025)
Prenuptial agreements are still often perceived negatively by some members of the public, because they are considered contrary to the value of decency and have the potential to cause prejudice and distrust between prospective spouses. Then, there are still a number of couples who only realize the urgency of making a prenuptial agreement after the marriage is held, so they assume that making the agreement is no longer juridically possible because the marriage bond has been valid and binding according to the provisions of the legislation. The purpose of this study is to determine and analyze the prenuptial agreement in the invitation laws and regulations in Indonesia as well as to determine and analyze the prenuptial agreement directly in marriage after the decision of the Constitutional Court. This research uses normative juridical legal research, which is one type of legal research methodology that bases its analysis on applicable laws and regulations and is relevant to the legal issues that are the focus of the research. Indonesia has three main legal bases governing pre-nuptial agreements, namely Law No. 16/2019 on the Amendment to Law No. 1/1974 on Marriage, the Compilation of Islamic Law (KHI), and the Civil Code (KUH Perdata) and coupled with Constitutional Court Decision No. 69/PUU-XIII/2015. These rules have regulated in detail the substance, terms, and procedures of this agreement. After the Constitutional Court Decision No. 69/PUU-XIII/2015, the agreement can also be made after the marriage takes place, as long as it does not violate the law, religion, and decency and does not harm third parties. The emergence of the Constitutional Court's decision No. 69/PUU/XII/2015, related to the pre-marital agreement that can be made by the husband and wife after the marriage takes place. The law gives freedom to everyone to make agreements in any form and content as long as it does not conflict with the provisions of laws and regulations, decency, and public order.